CAPACITY AND RESOURCE DEVELOPMENT IN PUBLIC HEALTH EDUCATION AND PROMOTION - Margaret N. Githae; Jacinta A. Opara (Medico Research Chronicles)
Health is the extent to which an individual or group is able, on the one hand, to realize aspirations and satisfy needs; and, on the other hand, to change or cope with the environment. Public health attempts to decipher what is going on within communities and determine how best to support their wellness efforts. Nevertheless, this cannot work without their input through decision making in a spirit of partnership. Hence the need to have a well-trained health workforce with practice experience on promoting as well as facilitating change in the communities. Our concern in this paper is that capacity building through health education and health promotion need to be in line with people-centered health principles.